2010
DOI: 10.1152/ajpheart.00782.2009
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin and thromboxane A2reciprocally interact to synergistically stimulate cardiac spinal afferents during myocardial ischemia

Abstract: Myocardial ischemia is a complex process leading to the simultaneous release of a number of mediators, including thromboxane A(2) (TxA(2)) and bradykinin (BK), that activate cardiac spinal afferents. The present study tested the hypothesis that TxA(2) and BK reciprocally interact to excite ischemically sensitive cardiac afferents. Nerve activity of single cardiac afferent units was recorded from the left sympathetic chain or rami communicantes (T(2)-T(5)) of anesthetized cats. Fifty-two ischemically sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In anesthetized rats, PGE 2 increased the discharge activity of single pulmonary C-fibers evoked by capsaicin, lactate, or adenosine (287). Another COX product, an analog of TXA 2 , enhanced the bradykinin-induced activation of ischemia-sensitive cardiac afferent C-fibers in anesthetized cats, whereas a TP receptor antagonist diminished the bradykinin response, suggesting a facilitatory role for endogenous TXA 2 (213). PGE 2 augmented CGRP release induced by bradykinin in the bovine dental pulp and isolated rat skin (29, 240).…”
Section: Effects Of Inflammatory Mediators On Peripheral Nociceptorsmentioning
confidence: 97%
“…In anesthetized rats, PGE 2 increased the discharge activity of single pulmonary C-fibers evoked by capsaicin, lactate, or adenosine (287). Another COX product, an analog of TXA 2 , enhanced the bradykinin-induced activation of ischemia-sensitive cardiac afferent C-fibers in anesthetized cats, whereas a TP receptor antagonist diminished the bradykinin response, suggesting a facilitatory role for endogenous TXA 2 (213). PGE 2 augmented CGRP release induced by bradykinin in the bovine dental pulp and isolated rat skin (29, 240).…”
Section: Effects Of Inflammatory Mediators On Peripheral Nociceptorsmentioning
confidence: 97%
“…BK (1-10 g/ml, 0.1 ml) was injected into the pericardial sack to evoke repetitive reflex increases in blood pressure and RSNA in response to BK. BK is produced during myocardial ischemia and participates in the activation of cardiac sympathetic afferents (15,57). Intrapericardial saline (1 ml) was applied three times to wash out BK after its application.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Our laboratory, as well as others, have reported that TxA2 stimulates vagal sensory nerves from the lung [11, 16, 18] as well as the heart [19, 22]. In addition we have shown that TxA2 stimulates spinal sensory nerves (group III and IV) from the hindlimb [13] while Fu et al has shown that TxA2 stimulates spinal afferent nerves innervating the heart [5, 7]. Since TxA2 is released from platelets and other cell types during tissue trauma or events that activate platelets, the stimulation of sensory nerves by TxA2 could play an important role in activation of reflexes during hemorrhage, inflammation, ischemia, tissue injury, or trauma.…”
Section: Introductionmentioning
confidence: 64%
“…Inhibition of TxA2R with various pharmacological antagonists have inhibited TxA2-induced neural stimulation using in vivo experiments of peripheral nerve recordings as well as using in vitro experiments with cultured neurons [1, 5, 21]. While the exact intracellular signaling mechanism for TxA2 excitation is not yet known, the mechanism likely involves calcium.…”
Section: Introductionmentioning
confidence: 99%